The Academic Discourse of Subjective Well-Being Within a Cultural Context: Methodological Limitations and Underlying Problems - Sbeih, Mirko Murad (ANIMA Indonesian Psychological Journal, 2013)
Cross-cultural comparisons of data obtained through self-reports underlie several methodological limitations to find objective determinants of Subjective Well-Being (SWB). Cultural relativism emphasizes that because societies vary in their values, individuals in them use different criteria for judging the performance of societies, which heavily influence respondent’s self-report measurements. Also translation of questionnaires might have an impact on SWB measurement results of self-reports. Furthermore there are several interfering factors like response biases and cultural differences which affect measuring SWB scores between societies. The methodological limitations and difficulties of cross-cultural measurements have been marginally addressed in empirical research and might impact SWB scaling across nations. Furthermore they might affect underlying comparisons and the validity of drawn conclusions within the academic discourse of SWB. It is necessary to consider these methodological issues in further studies to provide more clarity. Perbandingan lintas-budaya data yang diperoleh melalui laporan-diri mendasari keterbatasan metodologis untuk menemukan penentu objektif kenyamanan subjektif (KS). Relativisme budaya menekankan bahwa karena masyarakat bervariasi dalam nilai, individu di dalamnya memakai criteria berbeda untuk menilai tampilan masyarakat, yang amat memengaruhi pengukuran laporan-diri para responden. Demikian pula terjemahan kuesioner dapat berdampak terhadap hasil pengukuran laporan-diri. Selanjutnya terdapat beberapa faktor penyela seperti kerancuan respons dan perbedaan budaya yang memengaruhi pengukuran skor KS di antara masyarakat. Keterbatasan dan kesulitan metodologis pengukuran lintas-budaya telah diteliti secara terbatas dalam penelitian empiris dan dapat berdampak terhadap penyekalaan KS antar- negara. Selanjutnya hal tersebut juga dapat memengaruhi perbandingan dan validitas yang mendasarisimpulan yang ditarik dalam wacana akademik KS. Amatlah perlu mempertimbangkan isu-isu metodologis ini dalam studi-studi selanjutnya agar makin diperoleh kejelasan.